Estudo de caso: avaliação dos benefícios obtidos com a implantação de práticas de sustentabilidade e de eficiência energética em edificação pública - Santos, Fabricio Fontoura dos (2019)
Motivated by the history of poor use of natural resources in an inefficient way with serious social consequences, there is a need to implement sustainable solutions in purchases, projects and works executed by public agencies from the conception of a project, during its execution and even along of the building. Therefore, there is already a consensus that in public works one must make use of the concept of sustainable construction. For this reason, this research is about a case study in building of the public administration (B. P. A.), which aims to evaluate the main benefits obtained with the implementation of sustainability practices and energy efficiency applied in this building. Thus, by monitoring the energy produced in a photovoltaic system connected to the grid, an analysis of the merit indices of this photovoltaic installation and subsequent comparison with another reference system will be performed. In addition, by monitoring the water and energy consumption of the building, the savings obtained in relation to the estimated values will be calculated. Based on these results and the follow-up of the practical sustainability solutions adopted, to evaluate the tangible and intangible benefits achieved, so that this research can be adopted as a reference to help motivate, support and justify the adoption of such practices in purchasing processes public works, bidding, project preparation, works execution and contracting of services by agents of the public administration. Through this study, it was possible to prove the efficiency of the sustainability practices adopted since the results obtained showed significant savings: approximately 25% of water consumption savings, self-sufficiency to supply 100% of the energy consumption of the building and still produce surplus energy of more than 13% of its nominal consumption.